2015
DOI: 10.1016/j.jphotochem.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical investigation of electrocatalytic water oxidation by a mononuclear ruthenium complex in a homogeneous solution

Abstract: investigation of electrocatalytic water oxidation by a mononuclear ruthenium complex in a homogeneous solution, Journal of Photochemistry and Photobiology A: Chemistry http://dx.2 Highlight • Electrocatalytic water oxidation was studied by Potential-step chronocoulospectrometry. • [Ru(EtOtpy)(bpy)OH 2 ] 2+ can work for electrocatalytic water oxidation under weakly acidic conditions. • The rate-determining step for the electrocatalysis is oxidation of Ru IV =O to Ru V =O species. Abstract Electrochemical water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Berlinguette and Yagi groups have reported a series of mononuclear ruthenium complexes having [Ru II (tpy)(bpy)(H 2 O)] 2+ scaffold, wherein they revealed that electron‐withdrawing group suppresses the catalytic activity (e. g., TOF decreases), however increases the catalyst stability (TON) . Similar effects were also observed in a family of [Ru II (tpy‐R)(phen‐X)Cl] + complexes, where tpy‐R is the tridentate 4’‐(4‐methylmercaptophenyl)‐2,2’:6’,2’’‐terpyridine ligand, “phen” is 1,10‐phenanthroline, X is 5‐NO 2 or 5,6‐dimethyl or 3,4,7,8‐tetramethyl substituents …”
Section: Introductionmentioning
confidence: 72%
“…Berlinguette and Yagi groups have reported a series of mononuclear ruthenium complexes having [Ru II (tpy)(bpy)(H 2 O)] 2+ scaffold, wherein they revealed that electron‐withdrawing group suppresses the catalytic activity (e. g., TOF decreases), however increases the catalyst stability (TON) . Similar effects were also observed in a family of [Ru II (tpy‐R)(phen‐X)Cl] + complexes, where tpy‐R is the tridentate 4’‐(4‐methylmercaptophenyl)‐2,2’:6’,2’’‐terpyridine ligand, “phen” is 1,10‐phenanthroline, X is 5‐NO 2 or 5,6‐dimethyl or 3,4,7,8‐tetramethyl substituents …”
Section: Introductionmentioning
confidence: 72%
“…Comparisons between experimental vibrational spectra and density functional theory calculations confirmed the identity and structure of these two complexes. [4,5,22,[25][26][27][28][29][30] We show that we can selectively detectt he first two oxidized complexes in the proposed catalytic cycle by controlling the applied EC potential. However, such key reaction species are typically presenti no nly minor concentrations, necessitating as ensitive and selectivep robe, such as electrospray ionization mass spectrometry (ESI-MS).…”
mentioning
confidence: 83%
“…[1][2][3][4][5][6][7][8] MS identifies ions by their mass-to-charge (m/z)r atio, and with additional characterization tools such as collision-induced dissociation, can also provides ome structural information.C oupling spectroscopicc haracterization with MS, by schemes such as infraredm ultiple photon dissociation (IRMPD), [9] UV + IR resonant photodissociation, [10] and cryogenic ion vibrational predissociation (CIVP), [11] can further provide rich and detailed structural information as well as benchmarks fort heoretical methods used to characterizer eaction processes. [4,5,22,[25][26][27][28][29][30] We show that we can selectively detectt he first two oxidized complexes in the proposed catalytic cycle by controlling the applied EC potential. [12][13][14][15][16][17] Particularly,a ni n-line electrochemical (EC) cell can be coupled to an ESI source,s uch that intermediates and products formed under specific EC potentials can be sampled.…”
mentioning
confidence: 83%
“…Reversibility of the redox couple and the accompanied changes in the UV-vis spectrum in combination with the observation of clear isobestic points are a good indication that the electrochemically formed species are stable. 52,[59][60][61][62] In situ UV-vis spectroscopy of the bulk solution has also been employed to show the stability of the catalytic material. This, however, can be tricky.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%